Implementasi Pembelajaran Inklusi Bagi Anak Tunanetra di Yayasan Kesejahteraan Tuna Netra Islam - Hanif, Imamudin (HAWARI : Jurnal Pendidikan Agama dan Keagamaan Islam, 2025)
Inclusion education has been adapted to the abilities of ABK children, especially children who have deficiencies in their visual or visual senses. Tunanetra is one type of special needs that has a disturbance in the senses of vision. The purpose of this study is to describe the implementation of inclusive learning for children in Tunanetra Islamic Welfare Foundation which focuses on: 1) curriculum used and methods of forcing inclusive learning 2) how teachers in giving lessons of inclusion. The subjects of this research are students and class teachers. The research method used is qualitative descriptive research. The results of the survey showed that the implementation of the curriculum existing in Yaketunis uses an independent curricular with reference to access to learning that has already been adapted to ABK school standards. Teachers should strive to improve the quality of students. The learning model used by teachers to provide learning designed using their own methods in the classroom, such as adjusting the condition of students and arranging seats circularly and grouping. It can be concluded that this Yaketunis institution does not use special teachers and all teachers in the same ranks